Distributed path planning of a multi-robot system based on the neighborhood artificial potential field approach. (July 2019) - Matoui, Fethi; Boussaid, Boumedyen; Abdelkrim, Mohamed Naceur
The current study is set up to investigate the problem of planning the trajectories of a multi-robot system. It puts emphasis on the idea of using distributed architecture to plan the trajectories of a group of wheeled mobile robots. Each robot must be able to detect and avoid collision with both static and dynamic obstacles present in its environment/neighborhood. This study seeks to improve the artificial potential field (APF) method in order to have good trajectory planning of a multi-robot system. In order to address the purpose of this work, we employed the hybrid approach, which is a combination of three techniques: the APF method; the neighborhood system; and the notion of priority between the robots. Moreover, the minimum local problem is handled in this paper using the non-minimum speed algorithm. The implemented approach is adapted to solve the trajectory planning problem for a multi-robot system. So, the problem of intersection of robots at the same passage point is solved through using the method of assignment of priority between robots. We also used the neighborhood detection technique to reduce the influence area of each robot and to optimize the time of calculation. The overall system equations associated to the robots are updated at each time of simulation to react at any condition that might suddenly emerge. The approach is implemented with MATLAB/Simulink and Solidworks/Simmechanics.